Effect of Culture Media on the Yield and Protein Content of Pleurotus ostreatus (Jacq.) Kumm Mycelia - Kayise Hypercia Maseko; Thierry Regnier; Obiro Cuthbert Wokadala; Paul Bartels; Belinda Meiring (International Journal of Food Science)
The development of alternative proteins derived from fungi-based sources is gaining recognition due to their health benefits and lower environmental impact, compared to traditional animal-based sources. In this study, we investigated the culture conditions for Pleurotus ostreatus mycelia, focusing on the nutritional requirements and yield optimization using solid surface culture and liquid-state culture methods. Our findings indicate that optimal culture conditions involve glucose as the primary carbon source, with an initial pH of 6.0. By the eighth day of the culture period, media formulated with amaranth seed flour and Bambara groundnut flour yielded the highest mycelial protein content, characterized by a compact filamentous network with fewer open pores. Additionally, urea supplementation at 0.01% concentration on amaranth seed–based nutrient medium significantly increased the protein content from 31.4% to 38.7% (dry weight basis). The research findings contribute to the development of fungal-based proteins, which are essential in the production of sustainable food products.